Pengaruh Capital Intensity, Leverage, Institutional Ownership Dan Profitability Terhadap Perencanaan Pajak - Ningsih, Rini Kus Tresno; Josephine, Kezia (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of Capital Intensity, Leverage, Institutional Ownership, and Profitability on tax planning proxied by the Effective Tax Rate (ETR) in Transportation and Logistics sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This research used a quantitative method with secondary data obtained from company financial statements. Data analysis was conducted through descriptive statistics, classical assumption tests, multiple linear regression analysis, coefficient of determination, and hypothesis testing using SPSS version 27. The sample was determined using purposive sampling techniques involving 13 companies, resulting in 49 research data. The partial test results (t-test) showed that Capital Intensity, Leverage, and Institutional Ownership had no effect on tax planning. In contrast, Profitability had an effect on tax planning, indicating that the higher the company’s profitability, the greater the incentive to implement legal tax efficiency strategies in order to increase net profit. Therefore, Profitability is the main factor affecting tax planning in Transportation and Logistics sector companies during the 2021–2024 period.